Terapi Kelompok Terapeutik Teman Sebaya Terhadap Perilaku Pemilihan Jajan Sehat dan Kecukupan Energi Protein - Ruti Wiyati; Ani Kuswati; Esti Dwi Widayanti (Prodi Keperawatan Purwokerto, 2018)
The age of primary school children is the age of growth. The school environment can change the behavior of children to behave well. One of the efforts to improve the selection of healthy snacks in schools is by doing a Therapeutic group therapy. The therapy provides an opportunity for members to share experiences, help each other, to find a way to solve the problem and anticipate the problems that will be faced by teaching an effective way to control a healthy life. The purpose of this study was to determine the influence of Therapeutic Group Therapytowards Elementary School Children’s Behavior in Selecting Healthy Snack in District Sokaraja. The method of this research is quasi experimental pre-posttest with control group. The population in this study were the fourth grade students and the fifth grade students at SDN 1-2 of Karang kedawung, Karangnanas, Karangrau and Kalikidang. The sample in this study were 100 students, with a sample size 50 of intervention group and 50 of control group. The bivariate analysis using paired test and independent t-test. The results of the research showed a significant difference in the behavior of children in the selection of healthy snacks before and after the treatment in the intervention group (p = 0.000). In the control group, there are also significant differences in the child's behavior in the selection of healthy snacks before and after the treatment (p = 0:00). The recommendations of this research are expected to educate and change the behavior of children’s healthy snack in primary school.